1997
DOI: 10.1023/a:1006836703594
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pythium oligandrum Drechsler bearing spherical sporangia with complex subglobose elements was isolated for the first time in Egypt from agricultural field soil cultivated with alfalfa (Trifolium alexandrinum) in El-Minia, Egypt. This fungus was found to be an active bio-control agent against P. ultimum var. ultimum, the damping-off organism of wheat. In agar plates, P. oligandrum parasitized P. ultimum var. ultimum hyphae with the aid of thin haustorial branches or infection pegs, eventually leading to host de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In particular, with regard to diseases caused by oomycetes, most of the diseases where P. oligandrum has a control effect are caused by P. ultimum , which causes diseases on a broad range of crop species ( Thambugala et al, 2020 ). E.g., P. oligandrum has been reported to control pre- and post-emergence damping-off of wheat caused by P. ultimum ( Abdelzaher et al, 1997 ). To our knowledge, there are no reports in the literature of antagonism of P. oligandrum toward P. myriotylum or to the control of diseases caused by P. myriotylum .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, with regard to diseases caused by oomycetes, most of the diseases where P. oligandrum has a control effect are caused by P. ultimum , which causes diseases on a broad range of crop species ( Thambugala et al, 2020 ). E.g., P. oligandrum has been reported to control pre- and post-emergence damping-off of wheat caused by P. ultimum ( Abdelzaher et al, 1997 ). To our knowledge, there are no reports in the literature of antagonism of P. oligandrum toward P. myriotylum or to the control of diseases caused by P. myriotylum .…”
Section: Introductionmentioning
confidence: 99%
“…The first announcement of diseased wheat in Minia, Egypt was in 1997 when Abdelzaher and his co-workers reported damping-off of wheat caused by P. ultimum var. ultimum (Abdelzaher et al, 1997). They isolated P. ultimum var.…”
Section: Discussionmentioning
confidence: 99%
“…ultimum from the infected wheat plants while P. diclinum was only obtained from rhizosphere soil of the infected wheat seedlings. They also tested the pathogenicity of P. diclinum against wheat germinating seeds and seedlings and reported that P. diclinum was a non-pathogenic fungus (Abdelzaher et al, 1997). Our findings here revealed the occurrence of P. diclinum in a wheat field in Dear Attia village, Minia city, Egypt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations